DIAGNOSTIC CHALLENGE OF LEFT-SIDE APPENDICITIS DUE TO SITUS INVERSUS TOTALIS IN A LIMITED SETTING: A CASE REPORT - Hartanto Hartanto (Berkala Ilmiah Kedokteran Duta Wacana, 2021)
Background: Acute appendicitis is an acute abdominal case with a high incidence and often requires emergency surgical intervention. Situs inversus totalis is a rare congenital abnormality in which the thoracic and abdominal organs are totally transposed. Left-sided acute appendicitis (LSAA) is common in patients with congenital abnormalities such as situs inversus totalis. Diagnosis of LSAA is even more challenging, especially in peripheral areas which can lead to misdiagnosis and complications such as perforation or abscess. Imaging modalities are usually required to confirm the diagnosis. Case Presentation: A 21 years old male patient came to the emergency department with chief complaint of severe abdominal pain, starting 3 days earlier, localized to the epigastric area and migrating to the left lower quadrant. The patient also demonstrates fever, nausea and vomiting. Physical examination revealed an increasing abdominal wall rigidity and tenderness in the left lower quadrant as well as rebound tenderness. Laboratory tests revealed leucocytosis and increased neutrophils count. The patient underwent 3-position abdominal radiograph after chest X-ray showed dextrocardia. Exploratory laparotomy was done in this patient, showing a perforated appendix and totally transposed abdominal organs. Conclusion: Imaging modalities such as ultrasonography and abdominal CT Scan can be helpful in determining the diagnosis of LSAA and reduce the likelihood of misdiagnosis and complication. The possibility of LSAA and situs inversus should be suspected in a patient presenting with left lower quadrant abdominal pain with proven dextrocardia from chest X-ray. Keyword: Left-sided acute appendicitis, situs inversus totalis, dextrocardia